KEPEMIMPINAN PEMERINTAHAN TERHADAP PENINGKATAN PARTISIPASI MASYARAKAT PADA MUSYAWARAH PERENCANAAN PEMBANGUNAN DI DESA BETAO KECAMATAN PITU RIAWA KABUPATEN SIDENRENG RAPPANG - Ratna Ratna; Herman Dema (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
Abstract This study aims to determine: (1) Leadership of Village Heads in Betao Village, Pitu Riawa Sub-District, Sidenreng Rappang Regency (2) Community Participation in the Development Planning Conference in Betao Village, Pitu Riawa District, Sidenreng Rappang District. (3) Government Leadership towards Increased Community Participation in Delivering Development Planning in Betao Village, Pitu Riawa District, Sidenreng Rappang Regency. This research is a quantitative research using descriptive analysis. The population in this study were 72 people, namely BPD (Village Consultative Body), PKK Members, Hamlet Heads, Farmer Groups, Religious Leaders, Youth Figures, and Community Leaders. Sampling uses saturated samples for sampling techniques if all members of the population are used as samples. Data collection techniques in this study used (1) observation, (2) interviews, (3) questionnaires. The data analysis technique uses a Likert scale with the help of the frequency table and the SPSS program (Statistical Product and Service Solution) version 16.0.The results showed that the leadership of the Head of the Village in Betao Village, Pitu Subdistrict, the District of Sidenreng Rappang with a percentage value of 49.46% with a category of